Кредитні спілки на ринку фінансових послуг України - Луцишин, Олег Орестович; Lutsyshin, Oleg Orestovych (My University, 2011)
АНОТАЦІЯ Луцишин О. Кредитні спілки на ринку фінансових послуг України. - Рукопис. Дисертація на здобуття наукового ступеня кандидата економічних наук за спеціальністю 08.00.08 - гроші, фінанси і кредит. - Тернопільський національний еко¬номічний університет, Тернопіль, 2011. У дисертаційній роботі проведено комплексне дослідження теорії та практики ді-яльності кредитних спілок на ринку фшансових послуг України. Поглиблено теоре-тико-концептуальні засади ринку фшансових послуг, висвітлено його роль у контексті формування інституційних основ ринкової економіки. Розкрито кооперативну природу та інституційні особливості кредитної спілки як фінансового інституту ринку фінансо¬вих послуг. Обґрунтовано теоретичні основи організаційно-економічного механізму ді¬яльності кредитних спілок та узагальнено сучасні тенденції їх функціонування на ринку фшансових послуг України. Проаналізовано діючу практику та особливості формування капіталу кредитними спілками у контексті надання фінансових послуг. Розкрито особливості механізму трансформації заощаджень в інвестиції в процесі реалізації депозитних послуг кредит¬них спілок. Узагальнено соціально-економічні наслідки і виявлено проблемні аспекти діяльності кредитних спілок у сфері кредитування. На основі методики діагностичного дослідження фінансового стану кредитної спілки зроблено прогноз показників її фінансової стійкості, ділової активності та якості кредитної діяльності. Розроблено пропозиції щодо забезпечення фінансової стійкості кредитних спілок на ринку фінансових послуг. Запропоновано підходи до формування інфраструктури системи кредитної кооперації та вдосконалення пруденційного нагляду за діяльністю кредитних спілок на ринку фшансових послуг України. Ключові слова: ринок фінансових послуг, кредитна спілка, організаційно-еконо¬мічний механізм, власний, пайовий і резервний капітал, депозитні послуги, споживче кредитування, фінансова стійкість, пруденційний нагляд, апекс-інститут. ANNOTATION Lutsyshin О. Credit unions in the financial services market of Ukraine. -Manuscript. Dissertation on obtaining scientific level of Economic Sciences Candidate Degree in specialty of 08.00.08 - Money, Finance and Credit. - Ternopil National Economic University, Ternopil, 2011. This investigation examines the theory of credit unions as a financial intermediary in general, as well as the actual practical roles they play in the financial services markets in Ukraine. In the process, this work extends the conceptual framework in which credit unions are seen as playing a significant role in the intermediation of financial services. Particular attention is paid to the cooperative nature and the institutional peculiarities of credit unions as financial institutions, and inter alia the understanding of their role in the financial services market is extended. This document also delves in to the mechanism of credit creation and analyzes the economic forces and benefits unleashed by such a process, especially in terms of modern tendencies in Ukraine. The current practice and the peculiarities of credit unions' capital formation in the context of financial services provision are analyzed. In particular, this study extends the specifics of the transformation of savings into investments via the implementation process of credit unions' deposit services. Both the social and economic beneficial consequences are outlined here as well as the problematic aspects of credit unions' activity in the area of crediting are investigated. Diagnostic research is conducted on the basis of methodology specifying the financial conditions of a credit union in order to predict its financial stability, business activity and quality of credit activity data. Suggestions to provide greater the financial stability of credit unions in the market of financial services are developed in this document. Distinct approaches are suggested for the formation of the infrastructure of a credit cooperation system and for the improvement of the credit unions' activity in Ukraine via prudential supervision. Keywords: financial services market; credit union; organizational and economic mechanism; failure and reserve capital; deposit services; customer credit; financial stability; prudential supervision; apex-institute.
Credit unions in the financial services market of Ukraine
Keywords: ринок фінансових послуг; financial services market; кредитна спілка; credit union; організаційно-економічний механізм; organizational and economic mechanism; власний, пайовий і резервний капітал; failure and reserve capital; депозитні послуги; deposit services; споживче кредитування; customer credit; фінансова стійкість; financial stability; пруденційний нагляд; prudential supervision; апекс-інститут; apex-institute